2020
DOI: 10.1042/bsr20200676
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasma betaine levels and dysglycemia in patients with coronary artery disease

Abstract: Background: Dietary betaine intake was reported to associate with favorable profile of metabolic disorders. However, the role of circulating betaine in coronary artery disease (CAD) patients with dysglycemia is still unknown. This study aimed to investigate the potential associations between plasma betaine levels and dysglycemia in CAD patients. Methods: Total 307 subjects were enrolled in this study with 165 CAD patients (57 with dysglycemia and 108 with normal glycemia) and 142 age and sex matched controls (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“… 16 Previous results indicated that gut microbiota may contribute to production of betaine in mice fed with bran-enriched diets, and reduced plasma levels of betaine in human is positively associated with increased risks of metabolic disorders such as insulin resistance, coronary artery disease, and obesity. 16 , 69 , 70 However, its underlying mechanism is still poorly understood. In the present study, we showed that gut microbiota was crucial for the function of betaine on protecting against development of diet-induced obesity as well as obesity-associated complication, reasoning that supplementation of betaine failed to improve lipid and glucose metabolism, and stimulate browning of WAT of HFD-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Previous results indicated that gut microbiota may contribute to production of betaine in mice fed with bran-enriched diets, and reduced plasma levels of betaine in human is positively associated with increased risks of metabolic disorders such as insulin resistance, coronary artery disease, and obesity. 16 , 69 , 70 However, its underlying mechanism is still poorly understood. In the present study, we showed that gut microbiota was crucial for the function of betaine on protecting against development of diet-induced obesity as well as obesity-associated complication, reasoning that supplementation of betaine failed to improve lipid and glucose metabolism, and stimulate browning of WAT of HFD-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Greater betaine concentrations in coronary artery disease subjects have been found to be correlated with lower BP and HbA1c levels, and glucose, insulin, and TG concentrations ( 57 ). This is consistent with our results showing that those participants with a greater increase in betaine intake reduced HbA1c levels by more.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to TMAO, the relationship between plasma betaine and choline concentrations and cardiovascular events, including the end point of AMI end points, remains unclear. , The metabolism of betaine links several metabolites that play important roles in humans’ and other mammals’ health, including choline, homocysteine, and methionine involved in its catabolism . Betaine within the dietary intake range can reduce total homocysteine (tHcy) . For example, betaine is a rich component in wheat grains, especially in bran and aleurone, , which is considered as a potential contribution to the health value of whole grains .…”
Section: Introductionmentioning
confidence: 99%
“…Betaine is important to the remethylation of tHcy, a risk factor for cardiovascular disease, especially stroke . It is pointed out that betaine supplementation can reduce the fasting plasma tHcy level of healthy subjects by 15–20%, while after methionine loading, the plasma tHcy level decreases by 20–40%. , Betaine and choline can be used as dietary supplements for many purposes, including promoting heart health by reducing homocysteine, aiding digestion, and protecting liver. , In addition, other studies have reported that high intake of choline and betaine in diet is related to the reduction of inflammation . However, betaine and choline may have an adverse effect on the concentration of serum lipid, which may increase cardiovascular disease risk to some extent, though the increase of cardiovascular risk in patients with elevated choline and/or betaine levels was only observed in patients with concomitantly increased plasma TMAO concentrations .…”
Section: Introductionmentioning
confidence: 99%